Continuous and discrete mathematical modelling of the epidemic propagation - Ghemam Amara, Said (Université of eloued جامعة الوادي, 2025)
This thesis investigates the continuous and discrete mathematical modeling of epidemic propagation. It examines various epidemiological models, including Susceptible-Infected- Recovered (SIR), Susceptible-Infected-Recovered-Vaccinated (SIRV), and vector-borne dis- ease models like the Ross-Macdonald model. Key analyses involve determining equilibrium points and conducting stability analyses (local and global) for these continuous models, often using the basic reproduction number (R0) to understand conditions for disease persistence or eradication. The research further extends to the discretization of these models using finite difference methods, exploring the qualitative properties such as nonnegativity and monotonicity of the resulting discrete systems. Stability conditions for these discrete models, particularly for the discretized Ross-Macdonald model, are also investigated, supported by numerical simulations. The study aims to provide a comprehensive understanding of the mathemati- cal tools and frameworks used to model and analyze the spread of infectious diseases under different scenarios, including the impact of vaccination and vector transmission. Cette thèse étudie la modélisation mathématique continue et discrète de la propagation des épidémies. Elle examine divers modèles épidémiologiques, y compris les modèles Susceptible- Infecté-Rétabli (SIR), Susceptible-Infecté-Rétabli-Vacciné (SIRV), et les modèles de mal- adies à transmission vectorielle comme le modèle de Ross-Macdonald. Les analyses clés comprennent la détermination des points d’équilibre et la conduite d’analyses de stabilité (locale et globale) pour ces modèles continus, utilisant souvent le nombre de reproduction de base (R0) pour comprendre les conditions de persistance ou d’éradication de la maladie. La recherche s’étend en outre à la discrétisation de ces modèles par des méthodes de dif- férences finies, explorant les propriétés qualitatives telles que la non-négativité et la mono- tonie des systèmes discrets résultants. Les conditions de stabilité pour ces modèles discrets, en particulier pour le modèle de Ross-Macdonald discrétisé, sont également étudiées, étayées par des simulations numériques. L’étude vise à fournir une compréhension globale des outils et cadres mathématiques utilisés pour modéliser et analyser la propagation des maladies in- fectieuses dans différents scénarios, y compris l’impact de la vaccination et de la transmission vectorielle.
Fundamental and Applied Mathematics
Keywords: Susceptible-Infected-Recovered (SIR) model; Epidemic propagation; Vector-borne disease models; Ross-Macdonald model; The basic reproduction number; Nonnegativity; Mono- tonicity; Stability.; Les modèles Susceptible-Infecté-Rétabli (SIR); la propagation des épidémies; Les modèles de maladies à transmission vectorielle; Le modèle de Ross-Macdonald; Le nombre de repro- duction de base; La non-négativité; La monotonie; stabilité.